Evaluation and perception of MBBS first year students regarding early clinical exposure - Jiwane, Rekha; Gajbhiye, Vivekanand; Jiwane, Sushil (International Journal of Research in Medical Sciences, 2023)
Background: Evaluation and perception of MBBS first year students regarding early clinical exposure (ECE). The goals of ECE are to provide significance to basic sciences along with expansion of medical knowledge so as to establish the cognitive component of professional learning. Medical council of India has given new curriculum for MBBS for undergraduate medical education in which ECE is one of the reforms to improve quality of medical education. Methods: The study was conducted in the department of physiology, Peoples college of medical science and research centre Bhopal. The study duration was one year, 150 students of MBBS first year were included in study. All didactic lecture on systems was delivered mainly on respiratory physiology. It was vertically integrated with department of medicine and is followed by hospital visit. During hospital visit students was divided in 6 groups of 25. Clinicians was exposing the students to the relevant patients and discuss important symptoms and examination/findings on the patients. To assess whether the skills gained through ECE helped the students in the physiology classes of clinical examination, OSCE (Objectively structured clinical examination) was arranged before and after the intervention. Results: The post OSCE scores are better than pre OSCE scores. Perception of students toward ECE they have better understanding and retention of topic. Conclusions: ECE is a good tool for teaching and learning for first year MBBS.